Islamic Roots of Modern Pluralism: Indonesian Experience - Madjid, Nurcholish (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
Indonesia is one of the most pluralistic in the world. With is seventeen thousand island, large, and small, inhabited and uninhabited, Indonesia is the world's largest archipelago, and is a country with heterogeneous features. With about four hundred ethnic and linguistic groups, Indonesia is also very culturally diverse.DOI: 10.15408/sdi.v1i1.866